New perspectives on Austrian economics - Meijer, G. (Gerrit), 1938- (Routledge, 1995)
In recent years there has been a spectacular revival of interest in the economics of the Austrian school. The contributors illustrate the richness of the Austrian heritage and the continuing vitality of the Austrian school.